2022
DOI: 10.1002/ps.6779
|View full text |Cite
|
Sign up to set email alerts
|

Weed pressure determines the chemical profile of wheat (Triticum aestivum L.) and its allelochemicals potential

Abstract: BACKGROUND Common purslane (Portulaca oleracea) and annual ryegrass (Lolium rigidum) are important infesting weeds of field crops. Herbicides are mostly used for weed suppression, while their environmental toxicity and resistance in weeds against them demand considering alternative options, such as the use of allelopathic crops for weed management. Wheat is an important allelopathic crop and present research focused on the identification and quantification of benzoxazinoids (BXZs) and polyphenols (phenolic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 71 publications
5
11
0
Order By: Relevance
“…This demonstrates that the genetic progress in yield, obtained by breeding programs working under conventional agriculture, was also reflected, at least partially under organic agriculture. It is worth mentioning that in studies performed in the frame of the European research project ECOBREED cultivar URSITA was found to have also other characteristics that are important for organic agriculture, such as resistance to many bunt races, including the ones prevalent in Romania (Pfatrisch et al, 2022) and a higher capacity to exudate compounds with allelopatic effects on some weeds (Hussain et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that the genetic progress in yield, obtained by breeding programs working under conventional agriculture, was also reflected, at least partially under organic agriculture. It is worth mentioning that in studies performed in the frame of the European research project ECOBREED cultivar URSITA was found to have also other characteristics that are important for organic agriculture, such as resistance to many bunt races, including the ones prevalent in Romania (Pfatrisch et al, 2022) and a higher capacity to exudate compounds with allelopatic effects on some weeds (Hussain et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have specifically noted the allelopathic potential of wheat straw (Al Hamdi et al, 2001; Steinsiek et al, 1982), and rye mulch (Tabaglio et al, 2008) on weeds. Given that benzoxazinoid content within plant tissues is likely to be greater than levels in root exudate (Escobar & Niemeyer, 1993; Hussain et al, 2022; Stochmal et al, 2006), the application of cereal debris would increase allelochemical concentration and also delay its release as tissues decompose, potentially delaying degradation of these short‐lived compounds (e.g., Macías et al, 2004).…”
Section: Applying Allelopathy: Implementation In Weed Managementmentioning
confidence: 99%
“…This can be highly variable even between biotypes of the same species. However, Xu et al (2021) reported that relatively closely related rice cultivars can be more effective in competitive suppression of paddy weeds in spite of reduced allelochemical exudation, while another recent work appears to suggest that plants more functionally similar to the allelopathic species (and therefore potentially perceived as 'more of a threat' to their niche) will stimulate a stronger allelopathic response, at least in the case of wheat exuding benzoxazinoids (Hussain et al, 2022). Such findings indicate that the correct combination of crops or even cultivars may have potential to stimulate and maximize weed suppression through allelopathy due to these recognition interactions.…”
Section: Cover Cropping and Intercropping: Allelopathy As A Benefitmentioning
confidence: 99%
“…With mowing time, AN in soil decreased continuously, which hindered the formation of CP in leaves and reduced the forage quality (Table 2; Figure 1). First, wheat is an important allelopathic crop and some substances (such as benzoxazinoids and polyphenols) in its root exudates can inhibit the growth of its neighboring heterologous species (Lendzemo et al, 2009;Hussain et al, 2022). The accumulation of these allelopathic substances in the soil may inhibit the growth of C. esculentus.…”
Section: The Effects Of Rc On Plant Nutrient Accumulation and Forage ...mentioning
confidence: 99%